Treatment of Advanced Rectal Cancers: Cylindrical abdominoperineal excision of rectum - Lamichhane, Nirmal; Walker, Kenneth G.; Watson, Angus G.; Docherty, James (Nepalese Journal of Cancer, 2017)
Treatment for patients with locally advanced low lying rectal cancer differs significantly from patients with rectal cancer restricted to the mesorectum. Surgical resection will be the straightforward option for the early ones but multimodality treatment, including preoperative chemo-radiation and extended surgical resection will be the options for advanced ones. Cylindrical abdominoperineal excision of rectum (C-APER) along with possible composite pelvic organ resection is a surgical method to remove an adequate circumferential margin so to reduce the local recurrence rate and improve long term survival. Adequate preoperative imaging of the pelvis is therefore important to identify these patients and effort should be made to select those patients with advanced tumours with no systemic spread. In this article, we reviewed some consecutive cases of advanced rectal cancer to their immediate surgical outcome.